Evolution of power as an indicator of structural transformations: political and managerial aspect - V. V. Tyan (Управление)
The problem of the evolution of power as an indicator of structural transformations has been considered. An analysis of Russian practice allows us to draw a number of conclusions of interest to political science. A retrospective analysis of the evolution of power types provides additional knowledge about the political process and reveals an important political and managerial aspect for this study. Attention has been focused on the structural transformation of the current government.The interdependence of the subject of power and the object of power determines their interaction. It can be different (conflict, consensus, close) and characteristic of a certain type of political system (absolute and constitutional monarchy, presidential and parliamentary, presidential-parliamentary, confederative, federal republic). Monarchist rule with elements of coercion is doomed to conflict interaction, which predetermined the half-heartedness of all reforms in the Russian Empire. The traditional legitimization of power did not contribute to the improvement of interaction. Soviet rule, effective in mobilizing society, with real achievements, did not escape a critical number of negative indexes. Almost one hundred percent legitimization of the Soviet government did not remove doubts about its strength. The democratic legitimization of power requires it to implement a program of transformations in the system of power and society. The evolution of power is an accurate indicator of transformations in society. Political structuring remains the prerogative of the current government. Difficulties in the implementation of the program force the government to shift attention to maintaining stability in society.A well-structured power is a condition for its effective functioning. The efficiency of power (fighting corruption, ensuring of Gross Domestic Product (GDP) growth, solving social problems, etc.) is due to its ability to respond adequately to challenges and find consensus in decision-making in political turbulence.